Effect of Successful Breastfeeding Practices on Infant Development Outcomes - , Vinutha U. Muktamath; , Mouneshwari Kammar; , Prema Patil; , Shweta Biradar; , Sunita N H (Archives of Current Research International, 2024)
Breastfeeding is the most effective approach to nourish and promote the healthy growth of newborns, providing immune support. A differential design was used with the aim of studying the effect of successful breastfeeding practises on infant development outcomes such as physical, cognitive, language, psychomotor, and socio-emotional development. The study's population included 180 mother-infant dyads from northern Karnataka, India, with infants ranging in age from 3 to 24 months and mothers. The Socio-economic status (SES) scale developed by Aggarwal et al. (2005) and a self-structured questionnaire were used to document feeding practises, Bayley's Scale of Infant Development -III was used to assess developmental outcomes, and anthropometric tools. The results revealed that more than fifty per cent mothers-initiated breastfeeding within one hour while majority of mothers fed colostrum (77.80 %) and 53.33 per cent of mothers fed prelacteal feeds. When compared to complementarily and never breastfed children, infants exclusively breastfed during the first six months and fed for more than 12 months had better cognitive, linguistic and motor development. The influence of breastfeeding practices on socio-emotional development was not statistically significant. This indicates the need for family-based intervention to promote healthy nursing and proper weaning practices.